Comprehensive model applications for better understanding of pilot-scale membrane-aerated biofilm reactor performance. (April 2021) - Elsayed, Ahmed; Hurdle, Michael; Kim, Younggy
Graphical abstract: Highlights: Comprehensive MABR model was developed and calibrated using pilot operation data. Ammonia loading affects nitrification rate in MABR for municipal wastewater. Thick biofilms (>600 μm) for simultaneous nitrification and denitrification. Liquid film thickness does not affect nitrification but controls denitrification. Carbon-to-nitrogen ratio affects nitrification only for high-strength wastewater. Abstract: In membrane aerated biofilm reactors (MABR), simultaneous nitrification and denitrification (SND) are achieved by complicated biological reactions and mass transport in and between highly heterogeneous media: the air-permeable membrane; layered biofilms; liquid film; and bulk. To better understand large-scale MABR performance under real operation conditions, a comprehensive MABR model was developed and model calibration was completed with a pilot-scale MABR system. For the pilot system operated with municipal wastewater mixed with return activated sludge, the biofilm thickness was 1000–2000 μm, the liquid film thickness was 200–300 μm, and the diffusivity of the soluble components in the biofilm was 10–45 % of that in the infinite dilute solution. In the pilot operation, the ammonia removal rate was more rapid for higher ammonia loading rate, higher oxygen supply and lower pH conditions. Based on the model simulation results, we recommend that the biofilm be maintained thicker than 600 μm for SND. Thin liquid films (i.e., sufficient mixing conditions) are necessary for active denitrification as the slow transport of soluble organics through the liquid film limits denitrification; however, nitrification was hardly affected by thick liquid films because ammonia transport was sufficiently fast both in the liquid film and biofilm. A lower carbon-to-nitrogen (C/N) ratio enhanced nitrification only for high-strength wastewater (e.g., ammonia > 100 mg-N/L) because of more dominant growth of ammonia oxidizing bacteria (XAOB ) compared to heterotrophic bacteria (XH ). On the other hand, the C/N ratio does not affect nitrification when MABR is used for municipal wastewater treatment. Using the comprehensive model calibrated with pilot-scale MABR operation, the complicated biological reactions and material transport was elucidated for large scale MABR applications.